Guidelines Towards Sustainable Agriculture in Small Mediterranean Islands - A. Komnitsas, Kostas A; Doula, Maria K (European Journal of Sustainable Development, 2017)
The objective of the present paper is to provide guidelines towards sustainable agriculture in small islands, with emphasis on the cultivation of Pistacia vera L. in Aegina island, Greece. The guidelines refer among others to the characteristics of the island, pressures from other sectors such as tourism, current cultivation practices, land uses and take into account the risk for groundwater contamination. Special attention is paid on agricultural waste management at farm scale for the production of compost and biochar and their subsequent application to soils, in order to improve soil quality parameters (e.g soil organic matter, soil aggregate stability, water holding capacity, cation exchange capacity), increase soil carbon sequestration and reduce the risk of groundwater contamination. Also, the role of the most important stakeholders towards sustainable agriculture is emphasized and discussed. The proposed approach will assist towards identification of pressures, environmental hotspots, potential lack of synergy between stakeholders and thus indicate mid- and long-term measures to mitigate impacts and contribute to sustainable agriculture. Keywords: sustainability, agriculture, Pistacia vera L., compost, biochar